IDENTIFICATION OF HYBRID RICE TION OF HYBRID RICE TION OF HYBRID RICE (Oryza Sativa L.) AND ITS AND ITS PARENTAL LINES BASED ON MORPHOLOGICAL CHARACTERS - SHARMILA D. DEKA, MAMPI DEBBARMA; DEBOJIT SARMA (The Bioscan, 2018)
Identification and genetic purity testing of rice hybrids is crucial in harnessing their potential in carrying out scientific seed production and certification. The success of hybrid rice technology beside other factors depends on the production and timely supply of genetically homogenous seeds to farmer. This study is an attempt for characterization of local rice pollen parents and their hybrids using morphological markers. Seven qualitative and fourteen quantitative characters were recorded for morphological characterization of one Wild Abortive CMS lines (female) parent and ten pollen parents (male) and their ten hybrid combinations. Among seven qualitative characters five characters viz., leaf colour, stem internode colour, plant habit, Hull/grain colour decorticated grain shape and decorticated grain colour was suitable to use as markers to distinguish parental lines and their crosses (F1). All quantitative characters found suitable to use as morphological markers. Among the quantitative characters grain related characters are more suitable, hence can be used for quick and rapid identification of hybrids and their parent. Morphological characters were most useful for differentiating parental lines and hybrids and hence could be successfully employed for genetic purity testing.